Incorporating of Two Waste Materials for the Use in Fine-Grained Soil Stabilization - Hassnen Mosa Jafer; Zaid Hameed Majeed; Anmar Faleh Dulaimi (Salehan Institute of Higher Education, 2020)
The present experimental work briefly aimed to utilize two different waste materials; calcium carbide residue (CCR) and the locally available rice husk ash (RHA) to produce an eco-friendly binder for the use in fine-grained soil stabilization. The effect of different binary mixtures, produced by mixing CCR and RHA with different proportion, on the geotechnical properties of a fine-grained soil was investigated. For the unconfined compressive strength (UCS) test, the soil specimens were subjected to various curing periods (7, 21, 28 and 90 days). The microstructure of the soil treated with the optimum mixture was carried out by utilizing scanning electron microscopy (SEM) test. Results of UCS test showed an interesting growth after the treatment of binary mixtures relative to those samples treated with only CCR. Plasticity index (PI) was found to decrease noticeably with use of CCR only while further reductions in PI were achieved after the RHA incorporation. Clear variations in the microstructure of the treated soil were revealed from SEM testing approving the creation of cementitious products. The results of the current study indicated that the wastes utilized in this investigation could be potentially used as alternatives to the conventional binders and final disposition with economic and environmental advantages.